The Influence Of Innovation And Creativity Traders On Consumer's Repurchasing Interest In Merasi Stir-Fried Noodles Bengkulu City - Oryza Sativa Adi Pratama; Sri Ekowati (BIMA Journal (Business, Management, & Accounting Journal), 2021)
Empowering SMEs in the midst of globalization and high completion implies that SMEs should have the option to face difficulties around the world, for example, expanding item progress and administration, creating human resources and innovation, and growing market areas. The tittle of thiis research is the Influence of Innovation and Creativity of Traders on Consumer Re-Purchase Interest in Merasi Sauteed Noodles Bengkulu City. Thiis type of research is a type of descriptiive quantitative researrch, the object of this research is consumers in Mie Tumis Merasi which is precisely located on Jl. Manggis Raya, eastern circumference, Kel. Panorama, Kec. Singaran Pati, Kel. Bengkulu City. By sampling method using non probabilty technique nameely acciidental sampliing. The number of respondentts in thiis study was 130 people. Data collectiion method using questionnaire. By using data analysis techniques using Multiple Lineear Regression Analysis Test, and Hypothesis Test namely t and f Test. The results of this study can be concluded that the variables of Mie Tumis Merasi Innovation have a positive effeect on Consumer Re-Buy Interest, Merchant Creativity has a positiive effect on Consumer Re-Buy Interest, and Innovation and Creativity of Traders together have a positive and significant effect on Consumer Resend Interest.